2013
DOI: 10.1007/s12088-013-0424-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Immunological Regulations in Caenorhabditis elegans Infected with Salmonella enterica serovar Typhi

Abstract: Studies pertaining to Salmonella enterica serovar Typhimurium infection by utilizing model systems failed to mimic the essential aspects of immunity induced by Salmonella enterica serovar Typhi, as the determinants of innate immunity are distinct. The present study investigated the physiological and innate immune responses of S. Typhi infected Caenorhabditis elegans and also explored the Ty21a mediated immune enhancement in C. elegans. Ty21a is a known live vaccine for typhoidal infection in human beings. Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…CLEC-60 is a C-type lectin known to be regulated as part of the innate immune response. It is expressed in larval intestine and in adults in the Int8 and Int9 cells [ 54 , 55 ]. In control RNAi experiments, we observed the reported behavior.…”
Section: Resultsmentioning
confidence: 99%
“…CLEC-60 is a C-type lectin known to be regulated as part of the innate immune response. It is expressed in larval intestine and in adults in the Int8 and Int9 cells [ 54 , 55 ]. In control RNAi experiments, we observed the reported behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The innate immune system of C. elegans comprises evolutionarily conserved immune signaling pathways . The C‐type lectins ( clec‐60 and clec‐87 ) are evidenced to play a role in C. elegans innate immune system against Salmonella enterica serovar typhi infection by gene silencing approaches . The expression levels of clec‐60 , clec‐87 , and lys‐7 were significantly higher in C. elegans at the early stage of Shigella spp.…”
Section: Discussionmentioning
confidence: 99%
“…To briefly summarize, studies have shown that dsRNA longer than 25bp requires much lower concentrations than siRNA to have a similar RNAi effect and that this is due to Sid-2 being selective for length in uptake from the environment (Feinberg and Hunter, 2003;McEwan et al, 2012). However, nine studies were found reporting successful RNAi using siRNA soaking in nematodes, for example in M. incognita (Arguel et al, 2012;Dalzell et al, 2010a;Dalzell et al, 2010b), B. xylophilus (Ma et al, 2011) M. graminicolis , G. pallida (Dalzell et al, 2010a) and C. elegans (Sivamaruthi and Balamurugan, 2014).…”
Section: Srna Moleculementioning
confidence: 99%